Toga Garden Cultivation (Plants Drug Family) in Sukobendu Village, Mantup District, Lamongan - Putut Wijonarko, Gilang; Asmawati, Siti Nor (OJS Universitas Muhammadiyah Gresik, 2024)
In frame support development potency resource rural in Village Sukobendu in particular Hamlet Krajan 2, utilization And management environment can done with planting TOGA. Purpose of activity This is for increase knowledge And Skills inner society cultivating a garden TOGA. Method Which used in this activity is application steps which is implemented in cultivation park TOGA. devotion This face problem form lack of knowledge about caring for TOGA, so that solution Which offered is delivery about method nurse TOGA at a time demonstrate steps in planting TOGA. And results Which achieved on activities this gained a lot benefit like give knowledge about efficacy from a number of TOGA Which There is around public, method planting toga Which Good with practice making park TOGA Which can be utilized public around And method processing TOGA. Many kinds of solution Which offered is expected to be able overcome problem Which in facing by devotion.